Evidence of 100 TeV gamma-ray emission from HESS J1702-420: A new PeVatron candidate - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan; Martins, V. Barbosa; Barnacka, A.; et al. (Astronomy & Astrophysics, 2021)
Aims. The identification of PeVatrons, hadronic particle accelerators reaching the knee of the cosmic ray spectrum (few x 10(15) eV), is crucial to understand the origin of cosmic rays in the Galaxy. We provide an update on the unidentified source HESS J1702-420, a promising PeVatron candidate.
CRIS-Team WoS Importer:2021-10-15
Keywords: Cosmic rays; Gamma rays: general; Methods: data analysis; Radiation mechanisms: non-thermal

Fermi Large Area Telescope Performance after 10 Years of Operation - Ajello, M.; Atwood, W. B.; Axelsson, M.; Bagagli, R.; Bagni, M.; Baldini, L.; Bastieri, D.; Bellardi, F.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Supplement Series, 2021)
The Large Area Telescope (LAT), the primary instrument for the Fermi Gamma-ray Space Telescope (Fermi) mission, is an imaging, wide field-of-view, high-energy gamma-ray telescope, covering the energy range from 30 MeV to more than 300 GeV. We describe the performance of the instrument at the 10 yr milestone. LAT performance remains well within the specifications defined during the planning phase, validating the design choices and supporting the compelling case to extend the duration of the Fermi mission. The details provided here will be useful when designing the next generation of high-energy gamma-ray observatories.
CRIS-Team WoS Importer:2021-09-17

Incremental Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Baldini, L.; Ballet, J.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2022)
We present an incremental version (4FGL-DR3, for Data Release 3) of the fourth Fermi Large Area Telescope (LAT) catalog of gamma-ray sources. Based on the first 12 years of science data in the energy range from 50 MeV to 1 TeV, it contains 6658 sources. The analysis improves on that used for the 4FGL catalog over eight years of data: more sources are fit with curved spectra, we introduce a more robust spectral parameterization for pulsars, and we extend the spectral points to 1 TeV. The spectral parameters, spectral energy distributions, and associations are updated for all sources. Light curves are rebuilt for all sources with 1 yr intervals (not 2 month intervals). Among the 5064 original 4FGL sources, 16 were deleted, 112 are formally below the detection threshold over 12 yr (but are kept in the list), while 74 are newly associated, 10 have an improved association, and seven associations were withdrawn. Pulsars are split explicitly between young and millisecond pulsars. Pulsars and binaries newly detected in LAT sources, as well as more than 100 newly classified blazars, are reported. We add three extended sources and 1607 new point sources, mostly just above the detection threshold, among which eight are considered identified, and 699 have a plausible counterpart at other wavelengths. We discuss the degree-scale residuals to the global sky model and clusters of soft unassociated point sources close to the Galactic plane, which are possibly related to limitations of the interstellar emission model and missing extended sources.
CRIS-Team WoS Importer:2022-07-15

LMC N132D: A mature supernova remnant with a power-law gamma-ray spectrum extending beyond 8 TeV - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, Michael; Baghmanyan; Martins, V. Barbosa; et al. (Astronomy & Astrophysics, 2021)
Context. Supernova remnants (SNRs) are commonly thought to be the dominant sources of Galactic cosmic rays up to the knee of the cosmic-ray spectrum at a few PeV. Imaging Atmospheric Cherenkov Telescopes have revealed young SNRs as very-high-energy (VHE, >100 GeV) gamma-ray sources, but for only a few SNRs the hadronic cosmic-ray origin of their gamma-ray emission is indisputably established. In all these cases, the gamma-ray spectra exhibit a spectral cutoff at energies much below 100 TeV and thus do not reach the PeVatron regime. Aims. The aim of this work was to achieve a firm detection for the oxygen-rich SNR LMC N132D in the VHE gamma-ray domain with an extended set of data, and to clarify the spectral characteristics and the localization of the gamma-ray emission from this exceptionally powerful gamma-ray-emitting SNR. Methods. We analyzed 252 h of High Energy Stereoscopic System (H.E.S.S.) observations towards SNR N132D that were accumulated between December 2004 and March 2016 during a deep survey of the Large Magellanic Cloud, adding 104 h of observations to the previously published data set to ensure a > 5σ detection. To broaden the gamma-ray spectral coverage required for modeling the spectral energy distribution, an analysis of Fermi-LAT Pass 8 data was also included. Results. We unambiguously detect N132D at VHE with a significance of 5.7σ. We report the results of a detailed analysis of its spectrum and localization based on the extended H.E.S.S. data set. The joint analysis of the extended H.E.S.S and Fermi-LAT data results in a spectral energy distribution in the energy range from 1.7 GeV to 14.8 TeV, which suggests a high luminosity of N132D at GeV and TeV energies. We set a lower limit on a gamma-ray cutoff energy of 8 TeV with a confidence level of 95%. The new gamma-ray spectrum as well as multiwavelength observations of N132D when compared to physical models suggests a hadronic origin of the VHE gamma-ray emission. Conclusions. SNR N132D is a VHE gamma-ray source that shows a spectrum extending to the VHE domain without a spectral cutoff at a few TeV, unlike the younger oxygen-rich SNR Cassiopeia A. The gamma-ray emission is best explained by a dominant hadronic component formed by diffusive shock acceleration. The gamma-ray properties of N132D may be affected by an interaction with a nearby molecular cloud that partially lies inside the 95% confidence region of the source position.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Cosmic rays; Gamma rays: General; ISM: Supernova remnants

Relevance of jet magnetic field structure for blazar axionlike particle searches - Davies, James; Meyer, Manuel; Cotter, Garret (Physical Review D, 2021)
Many theories beyond the Standard Model of particle physics predict the existence of axionlike particles (ALPs) that mix with photons in the presence of a magnetic field. One prominent indirect method of searching for ALPs is to look for irregularities in blazar gamma-ray spectra caused by ALP-photon mixing in astrophysical magnetic fields. This requires the modeling of magnetic fields between Earth and the blazar. So far, only very simple models for the magnetic field in the blazar jet have been used. Here, we investigate the effects of more complicated jet magnetic field configurations on these spectral irregularities by imposing a magnetic field structure model onto the jet model proposed by Potter & Cotter. We simulate gamma-ray spectra of Mrk 501 with ALPs and fit them to ALP-less spectra, scanning the ALP and B-field configuration parameter space, and show that the jet can be an important mixing region, able to probe new ALP parameter space around ma 1-1000 neV and ga 5×10-12 GeV-1. However, reasonable (i.e., consistent with observation) changes of the magnetic field structure can have a large effect on the mixing. For jets in highly magnetized clusters, mixing in the cluster can overpower mixing in the jet. This means that the current constraints using mixing in the Perseus cluster are still valid.
CRIS-Team Scopus Importer:2021-01-22

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Search for Axionlike-Particle-Induced Prompt gamma-Ray Emission from Extragalactic Core-Collapse Supernovae with the Fermi Large Area Telescope - Meyer, Manuel; Petrushevska, Tanja (Physical Review Letters, 2020)
During a core-collapse supernova (SN), axionlike particles (ALPs) could be produced through the Primakoff process and subsequently convert into gamma rays in the magnetic field of the Milky Way. We do not find evidence for such a gamma-ray burst in observations of extragalactic SNe with the Fermi Large Area Telescope (LAT). The SN explosion times are estimated from optical light curves and we find a probability of about similar to 90% that the LAT observed at least one SN at the time of the core collapse. Under the assumption that at least one SN was contained within the LAT field of view, we exclude photon-ALP couplings greater than or similar to 2.6 x 10(-12) GeV-1 for ALP masses m(a) less than or similar to 3 x 10(-10) eV, improving previous limits from SN1987A by a factor of 2.
CRIS-Team WoS Importer:2020-06-26

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for the imprint of axion-like particles in the highest-energy photons of hard γ-ray blazars - Buehler, R.; Gallardo, G.; Maier, G.; Domínguez, A.; López, M.; Meyer, Manuel (Journal of Cosmology and Astroparticle Physics, 2020)
Axion-like particles (ALPs), predicted in theories beyond the Standard Model, can have observational effects on the transparency of the Universe to γ rays in the presence of magnetic fields. In this work, we search for effects compatible with the existence of ALPs with 80 months of data from the Fermi Large Area Telescope, by comparing the distributions of observed highest energy photons from sources beyond redshifts of z ≥ 0.1 with theoretical predictions in the presence of ALPs. We find no evidence for an increased γ-ray transparency due to ALPs and therefore we set limits on the ALPs parameters assuming a value of the intergalactic magnetic field strength of 1 nG. Photon-ALP couplings above 10-11 GeV-1 are excluded for ALP masses ma ≲ 3.0 neV . As the allowed magnetic field parameter space is large, we also test lower magnetic field strengths and no constraints can be set for B≤0.1 nG below the CAST limit. These constraints exclude a region of the parameter space not covered by other γ-ray telescopes and are compatible with limits imposed by other experiments.
CRIS-Team Scopus Importer:2020-10-16
Keywords: active galactic nuclei; gamma ray experiments

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

The detectability of fast gamma-ray blazar flares from magnetic reconnection with the Fermi Large Area Telescope - Petropoulou, Maria; Meyer, Manuel; Christie, Ian (Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021), 2022)
The physical mechanism for the production of fast gamma-ray variability in blazars remains debated. Plasmoids - magnetized quasi-circular structures of plasma formed self-consistently in reconnecting current sheets - are ideal candidates for the production of broadband variable non-thermal emission. Using state-of-the-art kinetic simulations of magnetic reconnection and radiative transfer calculations, we generate artificial gamma-ray light curves that would be observed with the Fermi Large Area Telescope (LAT). Our goal is to investigate if characteristic features of the theoretical light curves, such as the ultra-rapid gamma-ray flares predicted by the reconnection model, are detectable with the typical Fermi-LAT observations. A comparison with observed luminous and fast gamma-ray flares from flat spectrum radio quasars (FSRQs) reveals that magnetic reconnection events lead to comparable flux levels and variability patterns, especially when the reconnection layer is slightly misaligned with the line of sight. Emission from fast plasmoids moving close to the line of sight could explain fast variability on the time scales of minutes for which evidence has been found in observations of FSRQs. Our results motivate improvements in the existing reconnection model for blazars as well as dedicated searches for fast variability in LAT data as evidence for magnetic reconnection events.
CRIS-Team Scopus Importer:2024-12-16

The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope - Ajello, M.; Angioni, R.; Axelsson, M.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
The fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Gamma-ray Space Telescope Large Area Telescope (4LAC) between 2008 August 4 and 2016 August 2 contains . It includes 85% more sources than the previous 3LAC catalog based on 4 yr of data. AGNs represent at least 79% of the high-latitude sources in the fourth Fermi-Large Area Telescope Source Catalog (4FGL), which covers the energy range from 50 MeV to 1 TeV. In addition, gamma-ray AGNs are found at low Galactic latitudes. Most of the 4LAC AGNs are blazars (98%), while the remainder are other types of AGNs. The blazar population consists of 24% Flat Spectrum Radio Quasars (FSRQs), 38% BL Lac-type objects, and 38% blazar candidates of unknown types (BCUs). On average, FSRQs display softer spectra and stronger variability in the gamma-ray band than BL Lacs do, confirming previous findings. All AGNs detected by ground-based atmospheric Cerenkov telescopes are also found in the 4LAC.
CRIS-Team WoS Importer:2020-04-17

The Observability of Plasmoid-powered gamma-Ray Flares with the Fermi Large Area Telescope - Meyer, Manuel; Petropoulou, Maria; Christie, Ian M. (Astrophysical Journal, 2021)
The exact mechanism for the production of fast gamma-ray variability in blazars remains debated. Magnetic reconnection, in which plasmoids filled with relativistic particles and magnetic fields are formed, is a viable candidate to explain the broadband electromagnetic spectrum and variability of these objects. Using state-of-the-art magnetic reconnection simulations, we generate realistic gamma-ray light curves that would be observed with the Fermi Large Area Telescope. A comparison with observed gamma-ray flares from flat spectrum radio quasars (FSRQs) reveals that magnetic reconnection events lead to comparable flux levels and variability patterns, in particular, when the reconnection layer is slightly misaligned with the line of sight. Emission from fast plasmoids moving close to the line of sight could explain the fast variability on the timescales of minutes for which evidence has been found in observations of FSRQs. Our results motivate improvements in existing radiative transfer simulations as well as dedicated searches for fast variability as evidence for magnetic reconnection events.
CRIS-Team WoS Importer:2021-05-14